H0LiCOW – XI. A weak lensing measurement of the external convergence in the field of the lensed quasar B1608+656 using HST and Subaru deep imaging. Issue 1 (1st June 2020) - Tihhonova, O; Courbin, F; Harvey, D; Hilbert, S; Peel, A; Rusu, C E; Fassnacht, C D; Bonvin, V; Marshall, P J; Meylan, G; Sluse, D; Suyu, S H; et al.
ABSTRACT: We investigate the environment and line of sight (LoS) of the H0LiCOW ( H 0 Lenses in COSMOGRAIL's Wellspring) lens B1608+656 using Subaru Suprime-Cam and the Hubble Space Telescope ( HST ) to perform a weak lensing analysis. We compare three different methods to reconstruct the mass map of the field, i.e. the standard Kaiser–Squires inversion coupled with inpainting and Gaussian or wavelet filtering, and ${\rm {\small {glimpse}}}$, a method based on sparse regularization of the shear field. We find no substantial difference between the 2D mass reconstructions, but we find that the ground-based data are less sensitive to small-scale structures than the space-based observations. Marginalizing over the results obtained with all the reconstruction techniques applied to the two available HST filters F 606 W and F 814 W, we estimate the external convergence, κext, at the position of B1608+656 is $κ _{ext}= 0.11^{+0.06}_{-0.04}$, where the error bars correspond, respectively, to the 16th and 84th quartiles. This result is compatible with previous estimates using the number counts technique, suggesting that B1608+656 resides in an overdense LoS, but with a completely different technique. Using our mass reconstructions, we also compare the convergence at the position of several groups of galaxies in the field of B1608+656 with the mass measurements using various analytical mass profiles, and find that the weak lensing results favour truncated halo models.